A Comparative Review of Current Practices in Personality Assessment Norming. (March 2015) - Gaddis, Blaine H.; Foster, Jeff L.; Lemming, Matthew R.
<x xml:space="preserve">Abstract</x> Because consequential personnel decisions are often made by comparing an individual against a norm group, having accurate and representative norms is as important as having sound selection procedures. Existing standards provide specific guidance on selection procedures, but are less clear on norms. To fill this gap and define best practices, we (a) review existing literature and guidelines; (b) review current applied practices using 30 personality assessments offered in the United States, United Kingdom, and Canada; and (c) provide recommendations for strengthening existing guidelines and helping publishers develop, present, and apply norms for personality assessments.